2005
DOI: 10.1292/jvms.67.1223
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Histological Comparison on the Growth Patterns of Long-Bone Cortex in Young Calf, Pig, and Sheep

Abstract: ABSTRACT. Some young large farm animals show a laminar bone formation in the long-bone cortex. Such a laminar bone is gradually replaced by Haversian bone with osteons during their growth periods. In this preliminary study, we observed the transverse ground samples of tibia cortex in young calves, pigs, and sheep by backscattered electron imaging. The cortex bones of all the newborn (NB) animals were basically formed with laminar bone structures. The NB and 1-month-old (1-M) calves had a typical concentric str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 6 publications
2
36
0
Order By: Relevance
“…Yes (Ն6-mo) (120) Yes (32) Yes(1-yr) (120) Seasonal changes in BMD Possible (161,162) No No Likely Yes (163) E 2 decrease post-OX (see references in Table 2) Yes Variable: yes, no (24) Yes Yes…”
Section: ∼70-80mentioning
confidence: 99%
“…Yes (Ն6-mo) (120) Yes (32) Yes(1-yr) (120) Seasonal changes in BMD Possible (161,162) No No Likely Yes (163) E 2 decrease post-OX (see references in Table 2) Yes Variable: yes, no (24) Yes Yes…”
Section: ∼70-80mentioning
confidence: 99%
“…The laminar bone has been reported to form long-bone cortex in young calf, pig, sheep, and other young large animals [2,3,5,[8][9][10][11][12]15] including some larger dinosaurs [4,6]. One laminar bone unit consists of a hypercalcified primear line in the center, woven bone on both sides of the line, and lamellar bone with laminated appositional lines [2][3][4][5][6][9][10][11][12].…”
mentioning
confidence: 99%
“…One laminar bone unit consists of a hypercalcified primear line in the center, woven bone on both sides of the line, and lamellar bone with laminated appositional lines [2][3][4][5][6][9][10][11][12]. Such a laminar bone as calf bone-cortex is gradually replaced by Haversian bone with osteons during their growth periods [2,10,11,15]. Previously [9], we reported that an 11-year-old giant Holstein cow with dermal dysplasia (Cow 1) [7,14] showed a delayed osteon formation in a larger number of the remaining laminar bone volume compared with a 12-year-old Holstein normal cow (Cow 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations